Isolated Fallopian Tube Torsion in a Virgin Patient: A Case Report - Gökhan Boyraz; İlker Selçuk; Zafer Selçuk Tuncer (Medical Network, 2016)
The twisting of the adnexa; partially or totally around its vascular axis and causing hemorrhagic infarction is called adnexal torsion. Isolated torsion of the fallopian tube is a rare and uncommon pathology that has an incidence as 1 in 1.5 million women especially in the reproductive age. Here we describe an isolated torsion of the fallopian tube case with chronic pelvic pain.